2017
DOI: 10.1109/tmag.2017.2718485
|View full text |Cite
|
Sign up to set email alerts
|

Single-Sided Field-Free Line Generator Magnet for Multi-Dimensional Magnetic Particle Imaging

Abstract: Abstract. Magnetic Particle Imaging (MPI) is an emerging medical imaging modality that is not yet adopted by clinical practice. Most of the working MPI prototypes including commercial-grade research MPI scanners utilize cylindrical bores that limit the access to the scanner and the imaging volume. Recently a single-sided or an asymmetric device that is based on a field-free point (FFP) coplanar coil topology has been introduced that shows promise in alleviating access constraint issues. In this paper, we prese… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…This is an inherent property of single-sided scanners where the SF gradient decreases with the height. In principle, the gradient drop can be eliminated provided the implementation of the additional coils as described in [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an inherent property of single-sided scanners where the SF gradient decreases with the height. In principle, the gradient drop can be eliminated provided the implementation of the additional coils as described in [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…The single-sided MPI scanner confines all the hardware to one side of the device, which is beneficial, as it provides the patient with unrestricted access to the scanning area [ 13 ], although, with a limited penetration depth [ 14 ]. Unlike the original single-sided MPI scanner, which utilizes an FFP [ 13 , 15 , 16 ], we designed a single-sided device with a field-free line (FFL) [ 17 , 18 ] with a promise of a higher sensitivity [ 10 ] and more robust image reconstruction [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Scanners with an FFL have improved system sensitivity and a higher SNR with more particles in larger regions relative to scanners with an FFP, at the cost of the temporal resolution (Bulte, 2019;Top and Gungor, 2020). Additionally, Tonyushkin (2017) reported that the FFL setup has lower power consumption.…”
Section: Imaging Modalitymentioning
confidence: 99%
“…Single-sided devices have been explored in the field of MPI 29 , 38 , 86 , 87 ; for this clinical application, a single-sided, detector-only approach enables a simple, hand-held device. While MPI has no inherent depth attenuation, a single-sided coil has a sensitivity drop-off with distance from the detector, as illustrated in Fig.…”
Section: Hand-held Mp Detectormentioning
confidence: 99%